Aktualisasi Visi Teologi Politik Kristen O.Notohamidjojo Bagi Kepemimpinan Bangsa Suatu Kajian Reflektif terhadap Kekristenan di Indonesia dalam Mewujudkan Negara Pancasila - Floreanado Kilanta Sembiring (PAX HUMANA, 2015)
This writing is to effort to develop a bridge at upon "the culverts" of space and time between thinking of theological political of O Notohamidjojo in the contemporary christianity context in frame for Pancasila State realization. Pancasila as basic that aim to realize a social order that honour the differentiation, high uphold of unity, honour of human rights and freedom rights and social rights and also upholds social justice which on the line of vision of Kingdom God. In that correlation with christian's calling as citizen of Kingdom of God and Indonesian citizen, the Christianity of Indonesian have role as partner and prophet for every political instrument in Indonesia political produk that created as re+lection the aims of Pancasila that in a line with vision of God's Kingdom and to be antithesis of political product that indicated not re+lecting aim of Pancasila in Indonesia. The idea of Notohamidjojo is relevan to reappointed in Indonesian context that always to experience social change and the challenge especially for leadership of church and state for realization the task and responsibility. Keywords: O. Notohamidjojo, theological political, Pancasila, Indonesia, Indonesian christianity, Kongdom of God,leadership of church and state.